Influence of binder type and process parameters on the compression properties and microbial survival in diclofenac tablet formulations (Brazilian Journal of Pharmaceutical Sciences, 2011)
The influence of binder type and process parameters on the compression properties and microbial survival in diclofenac tablet formulations were studied using a novel gum from Albizia zygia. Tablets were produced from diclofenac formulations containing corn starch, lactose and dicalcium phosphate. Formulations were analyzed using the Heckel and Kawakita plots. Determination of microbial viability in the formulations was done on the compressed tablets of both contaminated and uncontaminated tablets prepared from formulations. Direct compression imparted a higher plasticity on the materials than the wet granulation method. Tablets produced by wet granulation presented with a higher crushing strength than those produced by the direct compression method. Significantly higher microbial survival (p< 0.05) was obtained in formulations prepared by direct compression. The percent survival of Bacillus subtilis spores decreased with increase in binder concentration. The study showed that Albizia gum is capable of imparting higher plasticity on materials and exhibited a higher reduction of microbial contaminant in the formulations. The direct compression method produced tablets of reduced viability of microbial contaminant.